Aesthetic outcomes of and anatomic reconstruction for Wassel type IV-D radial polydactyly using a modified Bilhaut-Cloquet procedure - Du, Zijing; Cui, Yan; Jiang, Hao; Han, Dong (Frontiers in Pediatrics, 2023)
Wassel type IV-D thumb duplication is the most complex form and anatomic reconstruction is difficult. The aim of this study was to create an aesthetically satisfactory anatomical reconstruction for Wassel type IV-D radial polydactyly thumbs using the modified Bilhaut-Cloquet procedure. Surgery was performed on 24 thumbs with Wassel type IV-D radial polydactyly. To align the joint surfaces, the proximal phalanxes were unequally joined, primarily on the ulnar, and the distal phalanx was either symmetrically joined or unequally joined via curvature osteotomy. The patients were followed up for 12–91 months. The interphalangeal joint remained stable in all cases. The average functional score was 13.5 points (maximum 14 points). The overall average cosmetic score was 3.3 (maximum 4 points). Our modification of the Bihaut-Cloquet procedure produced good functional results for patients with Wassel type IV-D radial polydactyly. This method is used to correct the alignment and to stabilize the interphalangeal joint in both hypoplastic thumbs.